2018
DOI: 10.3389/fimmu.2018.00457
|View full text |Cite
|
Sign up to set email alerts
|

The Soluble Form of Toll-Like Receptor 2 Is Elevated in Serum of Multiple Sclerosis Patients: A Novel Potential Disease Biomarker

Abstract: Multiple sclerosis (MS) is an immune-mediated inflammatory demyelinating disease of the central nervous system. It was previously shown that toll-like receptor (TLR)-2 signaling plays a key role in the murine experimental autoimmune encephalomyelitis (EAE) model of MS, and that TLR2-stimulation of regulatory T cells (Tregs) promotes their conversion to T helper 17 (Th17) cells. Here, we sought potential sources of TLR2 stimulation and evidence of TLR2 activity in MS patient clinical samples. Soluble TLR2 (sTLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 47 publications
1
29
0
1
Order By: Relevance
“…AP-1: activator protein-1; IRF-2: interferon regulatory factor 2; MAPK: mitogen-activated protein kinase; PI3K: phosphoinositide 3-kinase; RIP1: receptor-interacting protein; TLR: toll-like receptor; TRIF: TIR-domain-containing adapterinducing interferon-β; TRAM: TRIF-related adaptor molecule [Color figure can be viewed at wileyonlinelibrary.com] disorders including AD (E. Gambuzza et al, 2014;F. Su, Bai, Zhou, & Zhang, 2016), multiple sclerosis (Hossain et al, 2018;Ruggiero, 2012), epilepsy (Song et al, 2014;Wen et al, 2018), and stroke (Fadakar, Dadkhahfar, Esmaeili, & Rezaei, 2014;L. Zhang et al, 2012).…”
Section: Melatonin Inhibited Tlr4 Expression In Hypoxic Microgliamentioning
confidence: 99%
“…AP-1: activator protein-1; IRF-2: interferon regulatory factor 2; MAPK: mitogen-activated protein kinase; PI3K: phosphoinositide 3-kinase; RIP1: receptor-interacting protein; TLR: toll-like receptor; TRIF: TIR-domain-containing adapterinducing interferon-β; TRAM: TRIF-related adaptor molecule [Color figure can be viewed at wileyonlinelibrary.com] disorders including AD (E. Gambuzza et al, 2014;F. Su, Bai, Zhou, & Zhang, 2016), multiple sclerosis (Hossain et al, 2018;Ruggiero, 2012), epilepsy (Song et al, 2014;Wen et al, 2018), and stroke (Fadakar, Dadkhahfar, Esmaeili, & Rezaei, 2014;L. Zhang et al, 2012).…”
Section: Melatonin Inhibited Tlr4 Expression In Hypoxic Microgliamentioning
confidence: 99%
“…Rakusa et al, 2012;Kantor et al, 2015;Jahromi et al, 2014;Mahadeva et al, 2014Marrie et al, 2014Manack et al, 2011;Jick et al, 2015;Phé et al, 2016;Salinas-Casado et al, 2019. EAU guidelines, 2020Fowler et al;Rakusa et al, 2012Rakusa et al, 2012Clark and Welk, 2018;Shigemura et al, 2015;Jahromi et al, 2014Hossain et al, 2018Jahromi et al, 2014Jahromi et al, 2014. Phé et al, 2017Phé et al, 2016.…”
Section: Resultsmentioning
confidence: 99%
“…As soluble TLR2 is released from excessive TLR2 stimulation, the authors looked for potential stimulants and found data which suggested that bacteria responsible for UTIs were potent TLR2 stimulators (Gram-negative: Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Proteus vulgaris; Gram-positive: Enterococcus faecalis and Streptococcus pyogenes), relating recent UTIs to exacerbations of the disease. (Hossain et al, 2018).…”
Section: Other Findingsmentioning
confidence: 99%
“…They are highly specific neuronal proteins that are very stable in vitro [42]. Three major neurofilament subunits exist and based on their molecular mass they are named neurofilament heavy chain (200-220 kDa), neurofilament intermediate chain (145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160) and neurofilament light chain (68-70 kDa). NFL and NFH can be measured with enzyme-linked immunosorbent assays (ELISA) in CSF.…”
Section: Neurofilament Light Chain (Nfl) and Neurofilament Heavy Chaimentioning
confidence: 99%